2006
DOI: 10.1080/13882350600964667
|View full text |Cite
|
Sign up to set email alerts
|

Body Awareness and Dance-Based Training for Persons with Acquired Blindness—Effects on Balance and Gait Speed

Abstract: Background: Visual impairment may cause difficulties with motor skills involving postural control. As a part of rehabilitation, it is important to assess whether training can affect postural control in individuals with visual impairment. Aim: The purpose was to assess the effect of body awareness exercises and dance-based training on balance and gait speed in individuals of working age with acquired blindness. Method: Eight subjects with acquired blindness, aged 30-62 years, were recruited from the Low Vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Our results suggest that the low levels of physical activity previously demonstrated in childhood and adolescence continue into adulthood. It is important to note that although visual impairments seem to be one of the disabilities associated with a higher prevalence of sedentary lifestyles (Longmuir & Bar-Or, 2000), it has been shown that it is pos sible to motivate persons who are blind to be more active and that exercise programs could improve several components of physical fitness (Larsson & Frandin, 2006;Miszko, Ramsey, & Blasch, 2004;Surakka & Kivela, 2008).…”
Section: Counts Per Min)mentioning
confidence: 99%
“…Our results suggest that the low levels of physical activity previously demonstrated in childhood and adolescence continue into adulthood. It is important to note that although visual impairments seem to be one of the disabilities associated with a higher prevalence of sedentary lifestyles (Longmuir & Bar-Or, 2000), it has been shown that it is pos sible to motivate persons who are blind to be more active and that exercise programs could improve several components of physical fitness (Larsson & Frandin, 2006;Miszko, Ramsey, & Blasch, 2004;Surakka & Kivela, 2008).…”
Section: Counts Per Min)mentioning
confidence: 99%
“…Of these, three used the Otago exercise programme,30 33 34 three used general physical activity training programme aiming to improve balance29 35 36 and one used the Matter of Balance programme 37 38. The remaining interventions were based on other forms of physical activity including walking (n=1),31 tai chi (n=2),39 40 Alexander technique (n=1),25 26 Yoga (n=2),41 42 dance (n=1),43 aerobics (n=1)27 and core stability training (n=1) 28. One study used a falls prevention programme (FallProof) as a control, comparing to a dance-based intervention programme 32.…”
Section: Resultsmentioning
confidence: 99%
“…The first studies using the version published by Mattiasson‐Nilo et al (Table ) originated from the research group in Gothenburg, Sweden in a population study of elderly persons aiming at improving their PA level. The scale has then been used in other Swedish studies, such as in those by Rydwik as the first author regarding physical training in elderly persons, by Larsson & Frändin on dance‐based training in persons with acquired blindness, by Lammes et al regarding physical training in frail elderly persons, by Kollén et al on physical functioning in older persons with dizziness. Jarnlo & Nordell used it in a methodological study on a balance performance test on elderly people and Mosallanezhad et al when comparing physical activity and physical functioning in 75‐year‐old‐Swedish and Iranian persons.…”
Section: Resultsmentioning
confidence: 99%